From building to city level dynamic digital Twin: a review from data management perspective. Issue 9 (1st November 2022) - Yan, J; Lu, Q; Fang, Z; Li, N; Chen, L; Pitt, M
Abstract: The development of the digital twin (DT) has been focused greatly after the concept was brought from the manufacturing and aerospace areas. In the architectural, engineering, construction and facility management (AEC/FM) sector, DTs are capable of integrating heterogeneous metadata and cutting-edge technologies like artificial intelligence and machine learning to create a dynamic digital environment for various purposes. Although building information modelling (BIM) appears to be a significant contributor to DTs, one of the major limitations for DT development is how to construct and provide a shared data environment for all stakeholders to collaborate throughout the life cycle. Furthermore, as the stakeholders' requirements range of DTs expands from a single building to multiple buildings and regional/city levels, the information and data management gaps (e.g., BIM and GIS data integration) are more challenging and critical. To address these gaps, this paper aims to 1) review the current data management for building and city level DTs from a technical perspective; 2) summarise their major data management issues from building to city levels based on the review; 3) introduce the concept of city-level Common Data Environment (CDE) that addresses the issues identified above, and discuss the possibilities of developing a CDE for a dynamic city-level DT.